2011
DOI: 10.1289/ehp.1003371
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution and Blood Pressure in Adult Women Living in Rural China

Abstract: Background: Almost half of the world’s population uses coal and biomass fuels for domestic energy. Limited evidence suggests that exposure to air pollutants from indoor biomass combustion may be associated with elevated blood pressure (BP).Objective: Our aim was to assess the relationship between air pollution exposure from indoor biomass combustion and BP in women in rural China.Methods: We measured 24-hr personal integrated gravimetric exposure to fine particles < 2.5 µm in aerodynamic diameter (PM2.5) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
168
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(195 citation statements)
references
References 60 publications
20
168
7
Order By: Relevance
“…We measured each participant's height (centimeters), weight (kilograms), waist circumference (centimeters), and salt intake from cooked foods and used a pedometer to assess 24-h physical activity. Details on measurement of blood pressure and the other health and sociodemographic factors related to blood pressure are described elsewhere (11) and provided in Tables S1 and S2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We measured each participant's height (centimeters), weight (kilograms), waist circumference (centimeters), and salt intake from cooked foods and used a pedometer to assess 24-h physical activity. Details on measurement of blood pressure and the other health and sociodemographic factors related to blood pressure are described elsewhere (11) and provided in Tables S1 and S2.…”
Section: Methodsmentioning
confidence: 99%
“…We used multivariate regression models from our previous study on PM 2.5 exposure and blood pressure (11) so that any differences in the results could be unambiguously attributed to the difference in pollution variables. The following variables were included in all regression models: age, waist circumference, physical activity (daily number of steps), socioeconomic status, daily salt intake, day of the week and time of day of blood pressure measurement, and ambient air temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 High levels of cardiovascular disease, stroke risk, high blood pressure, etc., are found among adult females of rural areas where solid wood is used for cooking. 19 An allied research team conducted an epidemiological study to assess the real-life impact of biogas interventions on the risk of hypertension in rural Nepal considering two groups of cooks-(i) aged greater than 50 years and (ii) aged between 30-50 years. The study indicated that systolic blood pressure (SBP) increases with increasing age, diastolic blood pressure (DBP) decreases after 50 years, and lower SBP and DBP are more marked in biogas users than wood users.…”
mentioning
confidence: 99%
“…General increases in temperatures can magnify the adverse effects of air pollution on health (Kan, 2011). Indoor air pollution generated from burning biomass fuel, which is still widely used in rural China, also harms health (Baumgartner et al, 2011). China has amongst the highest incidence of premature mortality due to outdoor PM exposure and this could worsen without policy action (OECD, 2012a).…”
Section: Environmental Degradation Has Significant Costsmentioning
confidence: 99%